Karakteristik Ikan Koi Sebagai Sumber Penciptaan Karya Seni Grafis - Pramesti, Regita Ambar (Institut Seni Indonesia Yogyakarta, 2023)
A work of art can be produced through creative ideas obtained through childhood experiences up to the present time, the work of art itself can be a reflection of the creator of the artwork itself. The media itself becomes an influence on the creation of works of art, including the processes involved. The characteristics of koi fish are used as the basis for creating a work of art both in terms of behavior, color, and field composition to reflect human life based on the characteristics of koi fish. Through a variety of learning and direct experience, the artwork created is the result of observing everyday human life and then visualized through adjacent objects using the author's life. Koi is a type of freshwater fish that can easily adapt to its new environment. This fish can almost occupy almost any place. However, when moving to a new pond or container, you should not let the koi experience drastic changes. Fish must go through a period of quarantine and acclimatization before being placed in a new pond and mixed with other koi.The characteristics, colors, and behavior of the koi fish that are chosen to be kept by humans are considered a reflection of humans themselves, so that the characteristics of koi fish are symbols of human life. The works of art used to represent the above ideas use high-tech printing with canvas media.